Analysis of Customer Loyalty Affected by E-Service Quality Trough Customer Satisfaction - Rosanti, Anisa; Andini, Reza Valentina; Lindayani, Lindayani; Mubarok, Teten Mohamad Sapril; Setiawan, Rahyuniati (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
Customer loyalty is customer loyalty to the company for a product or brand in an indefinite period of time. If customer loyalty is low, there will be a decrease in marketing performance. The purposes of the study were to understand the e-service quality and customer on customer loyalty as marketing phenomenon. The population of this study was Indonesian society, at least users of the marketplace platform, individuals who have made transactions on the marketplace platform, researchers did not limit the population based on gender or age. The survey was sent via online and to face to face 483 randomly, there by individuals had the send probability of being selected from the population and the representing as sample. The data analysis technique in this quantitative study utilized statistical approach. The program used to analyze the data with the regression method was statistical product and service solution (SPSS) to meet the criteria for data analysis using regression, an interval scale was utilized. The technique of analyzing the data in this study was regression. The data obtained in this study is accurate and reliable with a significance level of 95%. Based on the results of research on the analysis of customer loyalty which is influenced by e-service quality through customer satisfaction, there is an influence between e-service quality and customer loyalty, then there is an influence between customer satisfaction on customer loyalty. Finally, there is an influence between e-service quality and customer satisfaction on customer loyalty. The test results in this study indicate that e-service quality and customer satisfaction have a big influence on customer loyalty, the better the quality of service provided will foster satisfaction for customers, when customers are satisfied, loyalty will be formed